Board expertise and the relationship between bank risk governance and performance - Lawrence Asare Boadi; Zangina Isshaq; Anthony Adu-Asare Idun (Cogent Business & Management, 2023)
The aim of this paper is to analyze the correlation between risk governance and bank performance while taking into consideration the influence of board expertise. The study argues that the connection between risk governance and performance depends on the level of expertise among board members who are integral to the risk governance framework. By analyzing data from 83 bank-year observations, which includes information from the bank focus database and hand-collected data from annual reports spanning the period from 2012 to 2021, this research employs panel models to analyze the impact of board expertise on bank risk governance and performance relationships among a selection of banks in Sub-Saharan Africa. The research reveals two significant findings: Firstly, the establishment of risk governance structures is negatively associated with bank performance. Secondly, there exists a negative association between the expertise of the board members and their performance. Finally, the study found the risk governance and performance relationship to be positively and significantly moderated by board expertise. The evidence in this study suggests that for risk governance structures to achieve the desired objectives of enhancing performance, board members must possess the required technical expertise. Regulators and shareholders may find this result useful in strengthening regulatory requirements on board expertise and in appointing board members, respectively.
Keywords: 650; board expertise; GMM; performance; risk governance; Sub-Saharan Africa